Effect of high-intensity exercise training on functional recovery after spinal cord injury - Li, Xinyan; Li, Qianxi; Li, Chenyu; Zhang, Chunjia; Qian, Jinghua; Zhang, Xin (Frontiers in Neurology, 2025)
Spinal cord injury (SCI) is a severe disorder of the central nervous system characterized by high prevalence and significant disability, imposing a substantial burden on patients and their families. In recent years, exercise training has gained prominence in the treatment of SCI due to its advantages, including low cost, high safety, ease of implementation, and significant efficacy. However, a consensus regarding the effects of various exercise training modalities and intensities on functional recovery in individuals with SCI remains elusive, and the efficacy and risks associated with high-intensity exercise training (HIET) are subjects of ongoing debate. Some studies have indicated that HIET offers superior therapeutic benefits, such as enhanced cardiovascular stress reflex sensitivity and increased release of neurotrophic factors, compared to moderate- or low-intensity exercise training. Nonetheless, HIET may entail risks, including secondary injuries, heightened inflammatory responses, and falls. This study reviews the positive and negative effects of HIET on various body systems in individuals with SCI, focusing on mechanisms such as neuroplasticity and immune regulation, to provide a theoretical basis and evidence for its prospective clinical application. Additionally, the limitations of existing studies are analyzed to inform recommendations and guidance for future research.